PERAN DPRD KABUPATEN GOWA DALAM PELAKSANAAN PERDA NOMOR 50 TAHUN 2001 PERSPEKTIF FIKIH SIYASAH - Prayudha, Anil Aqza; HL, Rahmatiah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar’iyyah, 2022)
This study aims to examine the role of the Regional People’s Representative Council (DPRD) of Gowa Regency in the implementation of Gowa Regional Regulation Number 50 of 2001 (Perda No. 50 of 2001). The research methods used fully use qualitative research. The results show that the Gowa Regency DPRD has the authority to supervise the implementation of every government policy, including the implementation of Perda No. 50 of 2001, and concretely, this role is carried out by supervising and ensuring that the government seriously performs its duties mandated by the Perda. From the perspective of siyasah jurisprudence, the government, including the DPRD, is obliged to prevent everything that can bring chaos, especially alcoholic beverages not only have the potential to damage health, but can also be the cause of actions that can disrupt order in society.